A Praxeological Analysis of The Grade II Arabic Textbook (KMA) for Madrasah Ibtidaiyah Students - Fera Purnama; Asep Sopian; Hikmah Maulani (Abjadia : International Journal of Education, 2026)
This study analyzes the Grade II Arabic textbook for Madrasah Ibtidaiyah (MI) using a praxeological framework, with a particular focus on maharah qirā’ah (reading skills). The research is motivated by limitations in task design and teaching techniques that have not fully supported students’ reading competence. Four tasks related to maharah qirā’ah were examined through a descriptive qualitative approach within the praxeological framework (task, technique, technology, theory). The findings reveal that task design remains heavily dependent on teacher direction, lacks explicit techniques, and has not fostered meaningful reading ability. The main obstacles identified are ontogenic (misalignment with students’ developmental stages) and didactic (ambiguity in implementation techniques), which restrict text comprehension. The study concludes that improvements in reading task design are necessary to ensure clarity, contextual relevance, and alignment with learners’ developmental levels. The novelty of this research lies in applying praxeology as an analytical tool, rarely employed in Arabic textbook studies at the MI level, thereby offering a new perspective for developing more effective teaching materials.